RTHP-07. TRANSCRIPTION FACTOR NETWORKS OF OLIGODENDROGLIOMAS (IDH-MUTANT AND 1p/19q CODELETED) TREATED WITH ADJUVANT RADIOTHERAPY OR OBSERVATION INFORMS PROGNOSIS. (5th November 2018) - So, Jonathan; Moraes, Fabio; Mamatjan, Yasin; Aldape, Kenneth; Zadeh, Gelareh
Abstract: Multicentre sequencing efforts have allowed for the molecular characterization of low-grade gliomas (LGG)(The Cancer Genome Atlas (TCGA), 2015). We sought to analyze TCGA gene expression datasets on oligodendrogliomas patients treated with adjuvant radiation (RT) or those observed to discover prognostic markers and pathways. METHODS: mRNA expression and clinical information of patients with oligodendroglioma were taken from the TCGA "Brain Lower Grade Glioma" provisional dataset. Transcription factor network reconstruction and analysis were performed using the R packages "RTN" and "RTNsurvival". Elastic net regularization and survival modeling were performed using the "biospear", "plsRCox", "survival" packages. RESULTS: From our cohort of 137 patients, 65 received adjuvant RT and 72 were observed. In the cohort that received adjuvant RT, a transcription factor activity signature was generated that was associated with shorter progression-free survival (PFS) (HR = 2.3, p < 0.001). This increased risk was not seen in patients who were observed (HR = 0.8, p = 0.3). Within the observation cohort, transcription factors associated with the circadian clock pathway (ARNTL, ARNTL2, CLOCK) predicted for poorer PFS (HR = 1.6, p < 0.01). A transcription factor activity signature was generated that was associated with poor PFS (HR = 1.8, p < 10 –5 ) and OS (HR = 1.7, p < 0.002) only for those patients who were observed. Median OS in the observation cohort negative for the signature was not reached, but was 70 months for patients positive for the signature. CONCLUSIONS: We identified a transcription factor activity signature associated with poor prognosis in patients with IDH mutated and 1p19q codeleted oligodendroglioma treated with adjuvant radiotherapy. These patients would be potential candidates for treatment intensification. A second signature was generated for patients who were more likely to progress on observation. This potentially identifies a cohort who would benefit from upfront adjuvant radiotherapy.